PERSEPSI CALON WAJIB PAJAK ATAS TINDAK PENGGELAPAN PAJAK - Lamia, Miranda; Morasa, Jenny; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Tax Evasion is a major problem in the Indonesian economics which related to state tax income. To know the perception of tax evasion done by taxpayers, we can observe it from the perception of future taxpayers like college student. The method used in this research is descriptive method, in the way of analyzing each data and then presented based on narrative data groups for conclusion to be mades. The result of this research is prospective student taxpayers of Politeknik Negeri Manado see that tax evasion from perceptions of tax system, feeling of justice and discrimination as an unreasonable act against the law.Keywords : Perception, Student, Prospective Student Future Taxpayers, Tax, Tax Evasion